2018
DOI: 10.5604/01.3001.0011.6139
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing Analysis of Endophytic Bacteria Diversity in Fruits of White and Red Pitayas from Three Different Origins

Abstract: Pitaya contains various types of polyphenols, flavonoid and vitamins which are beneficial for health and it is among the most important commercial tropical fruits worldwide. Endophytic bacteria might be beneficial for plant growth and yield. However, bacterial diversity in pitaya is poorly characterized. In this study, fruits of white and red pitayas from three different origins (Thailand, Vietnam and China) were chosen for endophytic bacteria diversity investigation by using Illumina HiSeq second-generation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A list of the most recent metagenomic studies [11][12][13][14][15][16][17]23,24,[32][33][34][35][36][37][38][39][40] has been prepared to summarize endophyte strains that can be potentially employed for specific plants and properties that have been enhanced (Table 1). It was demonstrated that plant growth promoting (PGP) abilities and biological nitrogen fixation, followed by the production of secondary metabolites and bioactive compounds, synthesis of fungicides and bactericides, and protection against environmental stresses are the most important benefits that are provided to plants by endophytes (Table 1).…”
Section: Next Generation Sequencing Platforms As An Effective Tool Inmentioning
confidence: 99%
“…A list of the most recent metagenomic studies [11][12][13][14][15][16][17]23,24,[32][33][34][35][36][37][38][39][40] has been prepared to summarize endophyte strains that can be potentially employed for specific plants and properties that have been enhanced (Table 1). It was demonstrated that plant growth promoting (PGP) abilities and biological nitrogen fixation, followed by the production of secondary metabolites and bioactive compounds, synthesis of fungicides and bactericides, and protection against environmental stresses are the most important benefits that are provided to plants by endophytes (Table 1).…”
Section: Next Generation Sequencing Platforms As An Effective Tool Inmentioning
confidence: 99%
“…Unlike traditional methods, high throughput sequencing can be used to obtain all endophytes (cultivated and uncultivated microbes) in plant tissues and can thus be used to comprehensively study the diversity and composition of endophytes in plants. Ren et al (2018) found that endophytic bacterial diversity at the species level was different between red and white pitayas. Tan et al (2017) found that continuous cropping practices for Chinese ginseng ( Panax notoginseng ) dramatically influenced the diversity and community structure of root endophytic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…All the samples were stored at 4 ° C and processed within 12 h. The whole plants were washed with tap water and distilled water several times, and then immersed in 70% ethanol (v/v) and sodium hypochlorite solution (0.5% available chlorine) for 1 min, respectively. After being washed with distilled water thoroughly three times, the whole plants were smashed into small pieces with a sterilized grinder ( Ren et al, 2018 ). The juice and residues were plated onto ISP2 agar (soytone 4 g, malt extract 10 g, glucose 4 g, agar 20 g, H 2 O 1000 ml, pH = 7.2) and Gause’s synthetic agar (soluble starch 20 g, sodium chloride 0.5 g, ferrous sulfate 0.01 g, potassium nitrate 1 g, sipotassium hydrogen phosphate 0.5 g, magnesium sulfate 0.5 g, agar 15 g, pH = 7.2) supplemented with nystatin and nalidixic acid (50 μg/ml each) to isolate actinomycetes strains.…”
Section: Methodsmentioning
confidence: 99%